Perjuangan Anak-Anak dalam Novel Si Anak Badai Karya Tere Liye - Ningsih, Okti Rahayu; Canrhas, Amril; Amrizal (UNIB Press, 2022)
The purpose of this study was to find and understand the struggles of children in solving problems in the novel Si Anak Badai by Tere Liye. The research method used in this research is descriptive qualitative. The data collection technique used in this research is literature study. Based on the results of research that has been carried out on the story in the novel